The attitudes of healthcare professionals towards nurse-physician collaboration - Eman Kamel Hossny; Hanaa Esmail Sabra (Wiley, 2021)
Abstract Aims The current study aims to examine the attitudes of healthcare professionals towards nurse-physician collaboration and to explore the level of satisfaction concerning the quality of collaboration among them. Design A descriptive comparative study design was used to demonstrate attitudes of 338 participants (158 internship nurses, 139 nurses and 41 physicians) working in intensive care units, surgical department and medical department. Methods Two instruments were used, socio‐demographic data sheet and Jefferson scale of attitude towards nurse-physician collaboration (JSANPC), it consisted of 15 items under 4 dimensions. Results The internship nurses have the high score (38.6%) in poor level of satisfaction regarding quality of collaboration between nurses and physicians comparing to staff nurses and physicians. Physicians are satisfied (61%) with the level of collaboration between them and nurses. Staff nurses have the high positive attitude (48.45 (4.03)) towards collaboration between nurses and physicians comparing to physicians and internship nurses. Conclusion Internship nurses were not satisfied with the level of collaboration between nurses and physicians.